Analysis of Soil Fertility on Revegetated Land after Nickel Mining in Tanjung Buli, East Halmahera - Drakel, Arman; Arifin, Hadi Susilo; Mansur, Irdika; Sundawati, Leti (Sangia Research Media and Publishing, 2021)
Soil fertility in land after nickel mining has a change in soil texture that changes both the profile color and the soil irregularity. Damage to the physical properties of the soil affects the soil nutrients needed by plants. Several physical and chemical properties of soil are influenced by texture including soil plasticity, soil permeability, ease of cultivation, lack of soil fertility and productivity. Stable soil fertility can support plant growth. Damage to the physical properties of the soil due to the loss of the soil interest (solum) by the ongoing washing of the soil. This results in the loss of some cations in soil colloids, resulting in low acidity (pH) of the soil becoming acidic. Cation Exchange Capacity (CEC) as the amount of charge of cations absorbed by soil colloids at a certain pH. Another factor in the decline in CEC is the decreasing number of cation nutrients that can be exchanged. The relationship with reclaimed and revegetated land is influenced by climatic factors with rainfall intensity. Soil fertility on revegetated land with CEC value and C-organic content was very low. Such soil fertility conditions are found in the revegetated zone with large leaf acacia (A. mangium) vegetation; sengon (P. falcataria); ketapang (T. catappa) and waru (H. tiliaceus). Soils that have low soil nutrient content are characterized by low organic matter content, very low available P content, and low cation exchange capacity.